Evaluation Of Malaria Surveillance System In Department Of Health District Sumbawa Besar - Zainuddin, Zainuddin; Hendrati, Lucia Yovita (Faculty of Public Health, 2014)
ABSTRACTMalaria is a public health problem that can affect infant mortality, under five, pregnant women and can reduce productivity. The annual parasite incidence from 2008 antil 2011showed malaria morbidity in Sumbawa district remain high. The Purpose of this study was to describe the implementation of Malaria Surveillance System at the District Health Office Lombok Sumbawa Besar. This study used a descriptive survey method. Subjects were malaria surveillance officer in district Health office, health centers, and hospitals. Research object is a document epidemiological surveillance report of malaria in 2013. Variables of this study is the implementation of malaria surveillance system (input, process, output) and surveillance system attributes. Data obtained from interviews and observations were analyzed descriptively. The results showed that the data type on input stage was not yet complete, the quantity of labor was complete but insufficient quality of human resources, facilities and sufficient funds were available. At stage of the data collection process employed W2 weekly report format and monthly report format, report formats and reporting lines were simple, completeness and monthly reports 100% W2, W2 reporting time liness was > 80% and monthly reports was > 90%, Analysis and interpretation of the data was done However the analysis of relationshif was conducted by 20% of primary health care. The resulting output is a description of endemicity areas, API and SPR are presented in tabular form, graph and maps. Dissemination of information is done in the form of reports, workshops and profiles. Feedback is done each month through coordination meeting, regular meetings and regular supervision. Surveillance evaluation system based on attributed surveillance showed its simplicity and acceptability, however sensitivity can not be assessed yet, low NPP 1.75%, report punctuality was > 80%. It is necessary the existence of expert epidemiologists (S2) and skilled epidemiologists (S1), training officer, coordination, and the role of public institutions and budgetary surveillance of malaria increased in all areas Sumbawa district health offices.Keywords: malaria surveillance systems, evaluation, surveillance attributes